Camillo Sitte - Gesamtausgabe. Schriften und Projekte Band 4 Schriften zu Pädagogik und Schulwesen - Semsroth, Klaus (2008)
In the Project P16901-G06 sponsored by the FWF, Camillo Sittes writings will be published for the first time in a "critical comprehensive edition", scheduled for six volumes. The basis for this edition is provided by the "Sitte Nachlass-Archiv" owned by the University of Technology, Vienna. The writings of volume four document Sittes writings in the field of pedagogy and school system. Camillo Sitte, who elsewise is predominantly known as urban theorist and urban planner only, earned his money as headmaster of vocational schools (i.e. Gewerbeschulen) and composed number of articles in journals, lectures and treatises. A central part in this volume consists of two lectures held for craftsmen and teachers in ceramics (1883) and cabinetmaking (1885). Those texts give ample evidence of Sitte's didactical methods in the fields of education in applied arts and complement the material provided in volume one about arts and crafts. Sitte combined several shorter articles and reviews with an unpublished paper of principles, the "Grundsätze zur Reform des Zeichenunterrichts", to a kind of draft for a systematics of drawing education. Moreover he takes a stand in a number of articles in newspapers and journals concerning the vocational school system, to whose formation and development he contributed vitally. Wolfgang Sonne and Ruth Hanisch put these texts into context, inform about the current state of research and establish connections to others of Camillo Sitte's fields of activity, which will be documented in the other volumes of this edition. The editorial work is done by Sonja Hnilica and Bernhard Langer. The Editors are Klaus Semsroth, Michael Mönninger and Christiane C. Collins.